Compliance With a Risk-Factor-Based Guideline for the Prevention of Neonatal Group B Streptococcal Sepsis - Maureen T. Fleming; Robert S. McDuffie; Kathy Russell; Susan Meikle (Hindawi Limited, 1997)
Objective: The purpose of this study was to determine the compliance rate with a maternal risk-factor-based guideline for the prevention of neonatal group B streptococcal (GBS) sepsis.